The Effectiveness of Paired-Share Gallery Walk (PSGW) on Students’ Critical Appraisal Skill (CAS) Improvement During The Medical Surgical Nursing Clinical Placement - Andina Setyawati; Mohammad Syafar Sangkala; Abdul Majid; Rini Rachmawaty (INDONESIAN NURSING JOURNAL OF EDUCATION AND CLINIC (INJEC), 2017)
Introductions: Less critical nurses in Indonesia may happen due to the lack of contribution of the nursing institutions in enhancing the critical thinking skill. The PSGW is one of clinical teaching methods that facilitates students to criticize the current literatures. This study aimed at identifying the effectiveness of the PSGW on students’ critical appraisal skill (CAS) improvement during the medical surgical nursing clinical placement.Methods: This quasy-experimental study used pre-posttest control group design. The subjects were students who are currently in the professional practice stage of medical surgical nursing area. They were randomly assigned into two groups: 30 subjects in intervention group who conducted PSGW and 30 subjects in control group who conducted standard method of journal presentation. CAS questionnaires developed by Oxford University had been used to measure students’ CAS in criticizing the journal. The data was analyzed using Wilcoxon, Mann-Whitney, paired  t-test, and independent t-test with level of significance at 0.05.Results: The intervention group experienced a significant increase in CAS score (p=0.0001) after performing the PSGW, while the control group experienced an insignificant decrease (p=0.596) after performing the standard method of journal reading. When comparing the posttest CAS of both groups, the result showed that there were significant differences in the posttest CAS scores (p=0.0001) with large effect size (r=0.63).Conclusions: The PSGW is an effective learning method for clinical teaching. Further study needs to be performed to investigate the effectiveness of PSGW on the academic learning process.